2008
DOI: 10.1677/joe-08-0302
|View full text |Cite
|
Sign up to set email alerts
|

Activin A reduces luteinisation of human luteinised granulosa cells and has opposing effects to human chorionic gonadotropin in vitro

Abstract: The transition of the dominant follicle into the corpus luteum is of fundamental reproductive importance. Luteinisation involves disparate changes in the gene expression of follicular granulosa cells that differentiate into the granulosa-lutein cells of the corpus luteum after the gonadotrophin surge. We have shown that activin and human chorionic gonadotropin (hCG) have opposing effects during luteolysis. Therefore, we hypothesised that activin A was an inhibitor of luteinisation that was blocked during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 73 publications
(77 reference statements)
4
22
0
Order By: Relevance
“…In the current study, we have shown that treatment of luteinising ovine granulosa cells with activin A reduced progesterone secretion; thus, the increased activin A concentrations observed around the time of oestrous in the reduced ES ewes may have resulted in poor luteal function in these ewes. Similar to what was observed in the current study, activin A has been shown to reduce luteinisation of granulosa cells in vitro in both humans and cattle (Myers et al 2008, Kayani et al 2009). Activin A also suppressed progesterone production in vitro from granulosa cells collected from preovulatory follicles in rats (Miro et al 1991).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, we have shown that treatment of luteinising ovine granulosa cells with activin A reduced progesterone secretion; thus, the increased activin A concentrations observed around the time of oestrous in the reduced ES ewes may have resulted in poor luteal function in these ewes. Similar to what was observed in the current study, activin A has been shown to reduce luteinisation of granulosa cells in vitro in both humans and cattle (Myers et al 2008, Kayani et al 2009). Activin A also suppressed progesterone production in vitro from granulosa cells collected from preovulatory follicles in rats (Miro et al 1991).…”
Section: Discussionsupporting
confidence: 89%
“…The activin pathway has been postulated to be involved in regulation of multiple reproductive processes including ovarian follicular development (Knight et al 2012), luteinisation of the follicular cells (Myers et al 2008, Kayani et al 2009), early embryo development (Rajput et al 2013) and uterine function during implantation of the conceptus (Singh et al 2011). As a member of the transforming growth factor beta superfamily of growth factors, activin forms from the dimerisation of two b-subunits of inhibin (INHB), with different combinations forming functionally different isoforms (Knight 1996, Mellor et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…However, inhibitory actions of Activin A on small secondary murine follicles have been reported [23]. Indeed, inhibitory roles of activin A have been documented in various cells and tissues such as CHO-K1 (Chinese hamster ovary) cell line [27], and more recently in the luteinisation of human granulosa cells [28]. The exact mechanism of Activin A's inhibitory action is not known but there is some evidence in mice that changes in intraovarian concentration of Activin affects follicle development in a stage dependent manner [23] and the data presented here agrees with that.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of 3b-HSD, a key enzyme for the synthesis of P 4 through pregnenolone, profoundly affects the level of P 4 secreted by the CL (Tuckey 2005). Two types of 11b-HSD isoforms are present in granulosa-lutein cells, and both enzymes may be upregulated by LH during luteinization (Thurton et al 2003, Myers et al 2008. The expressions of P450scc, 3b-HSD, and 11b-HSD in the luteal EC preparation were considerably lower than those in the total ovarian cell preparation that excluded ECs.…”
Section: Discussionmentioning
confidence: 99%